Effects of Oil on the Libyan Balance of Payments - MENES, AHMED (Dirasat in Economics and Business, 1980)
In addition to its direct gains the invest- ment in the oil industry might result in two kinds of indirect contribution to growth of national income. One is the Linkage effects and the other involves the creation of factors of production, which implies that in the pro- cess of its operation the new industry might contribute certain types of factors to the domestic economy, particularly foreign ex-change, investment resources (especially if large payments to government occur), and in the training of skilled labour and manage- ment. This article deals with the contribution of the oil industry to the Libyan balance of payments.